On the Intended and Unintended Consequences of Enhanced Border and Interior Immigration Enforcement: Evidence from Deportees - Catalina Amuedo-Dorantes; Susan Pozo (Institute for the Study of Labor (IZA), 2014)
Over the past decade, a number of federal and state policies intended to stem the flow of illegal immigration have been implemented. In this paper, we focus on two initiatives: (a) Operation Streamline, as an example of increased border enforcement by the federal government, and (b) state-level omnibus immigration laws, as an illustration of enhanced interior enforcement by state governments. We investigate whether these policies have reduced the intentions of deported immigrants to attempt a new unauthorized crossing. While state-level omnibus immigration laws reduce the proportion of deportees intending to attempt a new crossing, increased border enforcement has proven to be far less effective. In addition, we ascertain human costs associated with these policies. Our findings are mixed in this regard. Noteworthy is how the adoption of more stringent interior enforcement seems to result in a "herding" or "ganging-up" effect whereby the incidence of verbal and physical abuse rises with the number of states enacting such measures. Additionally, our estimates suggest that deportees are more likely to respond that they have risked their lives to cross into the United States as a result of enhanced border enforcement.
Keywords: F22; K42; 330; deportation; interior enforcement; border enforcement; treatment of deportees; re-migration intentions